Coating as well as preparation method and application thereof

By using the cross-linking reaction of phenolphthalein polyetherketone with matrix material and the combination of inorganic fillers in the coating, the adhesion, film formation and insulation problems of existing high-temperature resistant coatings in high temperature environments are solved, and efficient heat resistance and stability above 600°C are achieved.

CN119752275AActive Publication Date: 2025-04-04BYD CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202410575445.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-05-10
Publication Date
2025-04-04
Estimated Expiration
2044-05-10

AI Technical Summary

Technical Problem

Existing high-temperature resistant coatings have problems such as weak adhesion, poor film formation, poor insulation, poor high-temperature resistant and poor storage performance under high temperature environments.

Method used

A coating including a matrix material, phenolphthalein polyetherketone and inorganic filler is used to form a protective film by cross-linking of phenolphthalein polyetherketone with the matrix material, and to provide additional heat resistance at high temperatures using inorganic filler.

Benefits of technology

It achieves good adhesion, film formation and insulation in an environment above 600°C, and at the same time improves the high temperature resistance and storage stability of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119752275A_ABST
    Figure CN119752275A_ABST
Patent Text Reader

Abstract

The invention discloses a coating as well as a preparation method and application thereof. The coating comprises a matrix material, phenolphthalein polyether ketone and an inorganic filler. The coating provided by the invention has excellent high temperature resistance, insulativity and fire resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of coating technology, and in particular to a coating and a preparation method and application thereof. Background Art

[0002] High temperature resistant coatings generally refer to coatings that can maintain certain physical and mechanical properties without falling off at temperatures above 200°C, and are high-performance coatings that enable the protected substrate to function normally at higher temperatures. High temperature resistant coatings are generally divided into two categories: inorganic high temperature resistant coatings and organic high temperature resistant coatings. However, the existing inorganic high temperature resistant coatings have weak adhesion, resulting in poor film formation and poor insulation; while organic high temperature resistant coatings have poor high temperature resistance, are expensive, and have poor storage performance. Therefore, how to provide a coating with good insulation, high temperature resistance, strong adhesion, and good film formation has become the key. Summary of the invention

[0003] The purpose of this application is to provide a coating and a preparation method and application thereof to solve the problems of poor stability and high temperature resistance of existing coatings.

[0004] To achieve the purpose of this application, this application provides the following technical solutions:

[0005] In a first aspect, the present application provides a coating, which includes a base material, phenolphthalein type polyether ketone and an inorganic filler.

[0006] In one embodiment, the phenolphthalein type polyetherketone includes hydroxylated phenolphthalein type polyetherketone, and the hydroxylated phenolphthalein type polyetherketone reacts with the matrix material to form a cross-linked structure.

[0007] In one embodiment, the matrix material includes one or more of epoxy resin, polyester resin, polyurea-formaldehyde resin, polyurethane, polyimide, and phenolic resin.

[0008] In one embodiment, the mass ratio of the phenolphthalein polyetherketone, the base material and the inorganic filler is 1:(1-4):(7-20).

[0009] In one embodiment, the weight average molecular weight of the hydroxylated phenolphthalein type polyetherketone is 30,000 to 100,000.

[0010] In one embodiment, the inorganic filler includes glass powder, and in the coating, the mass proportion of the glass powder is 10% to 20%.

[0011] In one embodiment, the softening point of the glass powder is 320°C to 430°C.

[0012] In one embodiment, the average particle size of the glass powder is 5 μm to 30 μm.

[0013] In one embodiment, the inorganic filler includes boron nitride, and in the coating, the mass proportion of the boron nitride is 20% to 40%.

[0014] In one embodiment, the average particle size of the boron nitride is 10 μm to 30 μm.

[0015] In one embodiment, the inorganic filler includes a flame retardant filler, and in the coating, the mass proportion of the flame retardant filler is 1% to 15%.

[0016] In one embodiment, the flame retardant filler includes one or more of aluminum hydroxide, magnesium hydroxide, ceramic powder, and sericite.

[0017] In one embodiment, the inorganic filler includes an oxide filler, and in the coating, the mass proportion of the oxide filler is 10% to 30%.

[0018] In one embodiment, the oxide filler includes one or more of aluminum oxide, boron oxide, zirconium oxide, zinc oxide, and silicon powder.

[0019] In one embodiment, the coating further includes a curing agent, and in the coating, the mass proportion of the curing agent is 1% to 8%.

[0020] In one embodiment, the coating further comprises a coupling agent, and in the coating, the coupling agent accounts for 1% to 8% by mass.

[0021] In a second aspect, the present application provides a method for preparing a coating, comprising: dissolving phenolphthalein type polyether ketone in a solvent to obtain a polymer solution; mixing a base material, an inorganic filler and the polymer solution, and obtaining the coating after uniform mixing.

[0022] In a third aspect, the present application provides a sheet metal, comprising: a metal substrate and a coating applied on the metal substrate, wherein the coating is obtained by solidifying the coating described in the first aspect.

[0023] The coating provided in the present application includes a base material, a phenolphthalein polyether ketone and an inorganic filler, and can form a protective film layer after being applied. The coating has the following advantages: 1) The high molecular organic matter (phenolphthalein polyether ketone) has a good film-forming effect, the material itself is not easy to break brittlely, and it is not easy to crack before and after curing film formation, and it has good water resistance, so it has high stability; 2) The phenolphthalein polyether ketone itself has a high temperature resistance. By adding phenolphthalein polyether ketone to the coating, the temperature resistance of the coating can be significantly improved; 3) After the coating is film-formed, the inorganic filler can be combined with the base material and the phenolphthalein polyether ketone. After the phenolphthalein polyether ketone fails when exceeding the first temperature range, the inorganic filler further provides high temperature resistance (in the second temperature range), thereby improving the high temperature resistance of the coating. The combination of organic materials and inorganic materials can make the coating provided in the present application resistant to high temperatures up to 600°C.

[0024] In addition, the coating provided by the present application can also have the following effects: 1) high insulation, because the coating is obtained by mixing inorganic materials and organic materials, high molecular organic matter has insulating properties, and the inorganic materials used are mostly oxides and inorganic salts, which are poor conductors, so it can be applied to the surface of the metal substrate to play an insulating role; 2) fire retardancy, because phenolphthalein polyether ketone and inorganic filler have flame retardant properties, the coating can be applied to the surface of the metal substrate to play a fire retardant role; 3) strong adhesion, high molecular organic matter can be used as an excellent binder, so the collective material and phenolphthalein polyether ketone in the coating can provide higher bonding properties, and the shear strength of the coating prepared by the coating and the aluminum plate or stainless steel can reach more than 7MPa; 4) seismic and weather resistance, the film-forming coating has a cross-linked structure, and the polymer chains are connected by covalent bonds, and the connection strength is high, and it is not easy to break even at low temperatures, so the coating prepared by the coating does not crack under conditions of 600°C to air rapid cooling. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0026] Figure 1 This is the molecular structure diagram of phenolphthalein type polyetherketone;

[0027] Figure 2 It is the molecular structure diagram of hydroxylated phenolphthalein type polyetherketone;

[0028] Figure 3 The present invention is a flow chart of the preparation of a coating in an embodiment. DETAILED DESCRIPTION

[0029] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0030] Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used in this application and in the specification are only for the purpose of describing specific embodiments and are not intended to limit this application. The term "and / or" used in this application includes any and all combinations of one or more of the related listed items.

[0031] In conjunction with the accompanying drawings, some embodiments of the present application are described in detail below. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.

[0032] The following are explanations of the terms used in this article:

[0033] Weight average molecular weight (Mw): refers to the sum of the molecular weight of all molecules multiplied by their respective weight fractions. It is an important parameter for describing the distribution of high molecular weight. The test methods for weight average molecular weight include: gel permeation chromatography, light scattering, viscosity method and mass spectrometry.

[0034] Softening point: refers to the temperature at which a substance begins to soften. It is used to describe the specific point at which an amorphous polymer changes from a hard state to a plastic state at a certain temperature.

[0035] Average particle size: The particle size D50 of the inorganic filler also refers to the diameter of the cumulative 50% point; it is measured by laser particle size analysis, which uses a laser beam to illuminate the particles and determine the size distribution of the particles by analyzing the pattern of scattered light.

[0036] The present application provides a coating which can be used in a high temperature environment and has a high temperature resistance of up to 600° C. The coating comprises a base material, phenolphthalein type polyether ketone and an inorganic filler.

[0037] Specifically, the matrix material is a high molecular organic substance, which can be epoxy resin, polyester resin, polyurea-formaldehyde resin, polyurethane, polyimide, phenolic resin, etc. Phenolphthalein polyetherketone is a special polymer material (please refer to Figure 1Molecular structure of phenolphthalein polyetherketone), which combines the properties of phenolphthalein and polyetherketone. It is a polymer material composed of phenylene rings connected by ether bonds and carbonyl groups. This material has the advantages of high strength, high modulus, impact resistance, good thermal stability, good electrical insulation, corrosion resistance and good dimensional stability.

[0038] Optionally, the inorganic filler may include one or more of metal oxides (aluminum oxide, zirconium oxide, etc.), non-metal oxides (silicon dioxide, boron oxide, etc.), nitrides (boron nitride, silicon nitride, etc.), silicates, phosphates, ethyl silicate, etc. It should be explained that the high temperature resistance of the inorganic filler can reach 400°C to 1000°C, or even higher; and the hardness is generally higher than that of high molecular organic matter. After the high molecular organic matter fails at high temperature, the inorganic filler can further provide heat resistance.

[0039] The coating provided by the present application is an organic-inorganic hybrid composite high temperature resistant material, which is mainly composed of high molecular organic matter and added with inorganic fillers. Under high temperature environment, the film-forming material will be transformed from organic matter into inorganic film-forming material, thereby realizing the protection of metal substrates in a wide temperature range. The general film-forming mechanism is as follows: when the high molecular organic matter decomposes and carbonizes under heating conditions and loses sufficient bonding properties, the inorganic filler of the film-forming material melts and takes over the high molecular organic matter to continue to play the role of adhesion to the filler. The melting point of the film-forming material is adapted to the thermal decomposition temperature of the high molecular organic matter.

[0040] Further, the decomposition temperature of the phenolphthalein polyether ketone is in the first temperature range, the decomposition temperature of the inorganic filler is in the second temperature range, and the maximum value of the first temperature range is less than the maximum value of the second temperature range. The decomposition temperature of the phenolphthalein polyether ketone is in the first temperature range, and the first temperature range can be 400°C to 600°C, that is, within this temperature range, the phenolphthalein polyether ketone begins to decompose. The decomposition temperature of the inorganic filler is in the second temperature range, and the second temperature range can be 400°C to 1000°C. Therefore, the coating provided by the present invention can ensure thermal stability within the range of 400°C to 1000°C.

[0041] The coating provided in the present application includes a base material, a phenolphthalein polyether ketone and an inorganic filler, and can form a protective film layer after being applied. The coating has the following advantages: 1) The high molecular organic matter (phenolphthalein polyether ketone) has a good film-forming effect, the material itself is not easy to break, and it is not easy to crack before and after curing film formation, and it has good water resistance, so it has high stability; 2) Phenolphthalein polyether ketone itself has a high temperature resistance. By adding phenolphthalein polyether ketone to the coating, the heat resistance of the coating can be significantly improved; 3) After the coating is film-formed, the inorganic filler can be combined with the above-mentioned cross-linking structure, and after the cross-linking structure fails at high temperature, it further provides high temperature resistance, thereby improving the high temperature resistance of the coating. The combination of organic materials and inorganic materials can make the coating provided in the present application resistant to high temperatures up to 600°C.

[0042] In addition, the coating provided by the present application can also have the following effects: 1) high insulation, because the coating is obtained by mixing inorganic materials and organic materials, high molecular organic matter has insulating properties, and the inorganic materials used are mostly oxides and inorganic salts, which are poor conductors, so it can be applied to the surface of the metal substrate to play an insulating role; 2) fire retardancy, because phenolphthalein polyether ketone and inorganic filler have flame retardant properties, the coating can be applied to the surface of the metal substrate to play a fire retardant role; 3) strong adhesion, high molecular organic matter can be used as an excellent binder, so the collective material and phenolphthalein polyether ketone in the coating can provide higher bonding properties, and the shear strength of the coating prepared by the coating and the aluminum plate or stainless steel can reach more than 7MPa; 4) seismic and weather resistance, the film-forming coating has a cross-linked structure, and the polymer chains are connected by covalent bonds, and the connection strength is high, and it is not easy to break even at low temperatures, so the coating prepared by the coating does not crack under conditions of 600°C to air rapid cooling.

[0043] In one implementation, please refer to Figure 2 The phenolphthalein type polyetherketone includes a hydroxylated phenolphthalein type polyetherketone, and the hydroxylated phenolphthalein type polyetherketone reacts with a base material to form a cross-linked structure. Specifically, Figure 1 and Figure 2 The difference between phenolphthalein polyether ketone and hydroxylated phenolphthalein polyether ketone can be seen in the figure. The hydroxylated phenolphthalein polyether ketone with higher heat resistance is obtained by converting the carbonyl position of the phenolphthalein polyether ketone into a hydroxyl group.

[0044] During the synthesis process, the original chemical properties of hydroxylated phenolphthalein polyetherketone are changed by introducing hydroxyl functional groups. Hydroxylated phenolphthalein polyetherketone exhibits good thermal stability, mechanical strength and specific chemical reactivity, and is suitable for various extreme environments of high temperature, high pressure or chemical corrosion.

[0045] It is understandable that the temperature resistance of ordinary base materials is generally between 100℃ and 400℃. For polymers with cross-linked structures, the thermal stability, mechanical strength and chemical resistance of the polymers are significantly improved, and as the degree of cross-linking increases, the free movement of the chain segments will decrease, resulting in a decrease in plasticity and elongation, while the strength, elasticity and hardness will increase. The hydroxyl groups on the hydroxylated phenolphthalein polyetherketone have high reactivity and can become a "connector" for the base material. The hydroxylated phenolphthalein polyetherketone reacts with the polymer segments on the base material and connects the molecular chains to form a large-scale three-dimensional network structure, which can significantly improve the high temperature resistance of the coating.

[0046] Phenolphthalein polyether ketone is used as a "connector" to form a cross-linked structure with the base material. After the coating is formed into a film, the phenolphthalein polyether ketone and the base material can play a high temperature resistance role before 450°C to 500°C; at the same time, the coating provided in the present application can also have corrosion resistance, because after the base material and the phenolphthalein polyether ketone are cross-linked, the tolerance to inorganic / organic solvents is further improved, and the inorganic filler does not react with the organic solvent, so that the coating can provide good corrosion resistance for the metal substrate.

[0047] In one embodiment, in the coating, the mass ratio of phenolphthalein type polyetherketone, base material and inorganic filler is 1:(1-4):(7-20).

[0048] Optionally, the mass ratio of phenolphthalein polyether ketone, matrix material and inorganic filler can be 1:1:(7-20), 1:2:(7-20), 1:3:(7-20), 1:4:(7-20), 1:(1-4):7, 1:(1-4):10, 1:(1-4):12, 1:(1-4):14, 1:(1-4):16, 1:(1-4):18, 1:(1-4):20.

[0049] In one embodiment, in the coating, the mass proportion of phenolphthalein polyetherketone can be 5% to 15%. Optionally, the mass proportion of phenolphthalein polyetherketone can be 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%. If the mass proportion of phenolphthalein polyetherketone is within the above range, it can ensure that the phenolphthalein polyetherketone improves the temperature resistance of the coating, or can give full play to the role of the functional groups in the hydroxylated phenolphthalein polyetherketone to form a cross-linked structure with better properties with the matrix material.

[0050] In one embodiment, the weight average molecular weight of the hydroxylated phenolphthalein polyether ketone is 30000 to 100000. Optionally, the weight average molecular weight of the hydroxylated phenolphthalein polyether ketone can be 30000, 40000, 50000, 60000, 70000, 80000, 90000, 100000. When the weight average molecular weight of the hydroxylated phenolphthalein polyether ketone is within the above range, the hydroxylated phenolphthalein polyether ketone can be ensured to have a higher structural strength and higher temperature resistance; at the same time, it also has relatively excellent solubility in a specific solvent, which is convenient for processing.

[0051] In one embodiment, the matrix material is epoxy resin, and in the coating, the mass proportion of epoxy resin can be 10% to 20%. Optionally, the mass proportion of epoxy resin can be 10%, 11%, 12%, 13%, 14%, 5%, 20%, 16%, 17%, 18%, 19%, 20%. When the mass proportion of epoxy resin is within the above range, it can be ensured that the coating has enhanced film-forming properties, good dispersibility of the coating, and can form a cross-linked structure.

[0052] Optionally, the type of epoxy resin may be E-44, E-51, E-42, or E-54.

[0053] It is understandable that due to the chemical activity of the epoxy group, it can be opened with a variety of compounds containing active hydrogen, cured and cross-linked to form a network structure, so it is a thermosetting resin. The physical and chemical properties of epoxy resin are very excellent, including heat resistance, chemical stability, electrical insulation and mechanical strength. It can still maintain stability in extreme environments such as high temperature and high pressure, and the required performance can be obtained by adjusting the formula. In addition, the cured epoxy resin products have the characteristics of high cleanliness, not easy to be contaminated by dust, rich colors, waterproof and mildew-proof, good toughness, and not easy to corrode. But please note that the high temperature resistance of epoxy resin is relatively poor and it is easy to scratch, so you need to pay attention to its applicable environmental conditions when using it.

[0054] In one embodiment, the inorganic filler includes glass powder. Specifically, glass powder is an inorganic amorphous hard ultrafine particle powder with a white powder appearance. Its production raw materials mainly include high-temperature high-purity silicon oxide and aluminum oxide, etc. After an ultra-clean production process, a disordered glass transparent powder is formed. This material has stable chemical properties and exhibits acid and alkali resistance, chemical inertness, low expansion coefficient and other characteristics, making it a super weather-resistant powder material.

[0055] The purpose of using glass powder in the present application is: 1) to use glass powder to increase the upper limit of high temperature resistance of the coating. It is understandable that glass powder, as an inorganic material, has excellent high temperature resistance itself and can continue to provide heat resistance after the organic material fails; 2) hydroxylated phenolphthalein polyether ketone and glass powder are combined as the main film-forming materials. Before 450-500°C, hydroxylated phenolphthalein polyether ketone mainly plays a role in high temperature resistance, and after exceeding 500°C, glass powder mainly plays a role in high temperature resistance. The prepared coating can withstand up to 600°C; 3) glass powder can be used as a "binder" for other inorganic fillers. At high temperature, the glass powder can bond other inorganic fillers together after melting, thereby ensuring that the coating will not crack or break.

[0056] In one embodiment, in the coating, the mass proportion of glass powder is 10% to 20%. Optionally, the mass proportion of glass powder can be 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%.

[0057] In one embodiment, the softening point of the glass powder is 320° C. to 430° C. Optionally, the softening point of the glass powder may be 320° C., 330° C., 340° C., 350° C., 360° C., 370° C., 380° C., 390° C., 400° C., 410° C., 420° C., or 430° C.

[0058] In one embodiment, the average particle size of the glass powder is 5 μm to 30 μm. Optionally, the average particle size of the glass powder can be 5 μm, 6 μm, 8 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, 20 μm, 22 μm, 24 μm, 26 μm, 28 μm, or 30 μm.

[0059] In one embodiment, the inorganic filler includes boron nitride, and in the coating, the mass proportion of boron nitride is 20% to 40%. Optionally, the mass proportion of boron nitride can be 20%, 22%, 24%, 26%, 28%, 30%, 32%, 34%, 36%, 37%, or 40%.

[0060] In one embodiment, the average particle size of the boron nitride is 10 μm to 30 μm. The average particle size of the boron nitride can be 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, 20 μm, 22 μm, 24 μm, 26 μm, 28 μm, or 30 μm.

[0061] In one embodiment, the inorganic filler includes a flame retardant filler, and in the coating, the mass proportion of the flame retardant filler is 1% to 15%. Optionally, the mass proportion of the flame retardant filler can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%. The flame retardant filler is mainly used for flame retardancy, which can prevent the coating from burning after forming a coating.

[0062] In one embodiment, the flame retardant filler includes one or more of aluminum hydroxide, magnesium hydroxide, ceramic powder, and sericite.

[0063] In one embodiment, the flame retardant filler includes aluminum hydroxide, and in the coating, the mass proportion of aluminum hydroxide is 1% to 8%. Optionally, the mass proportion of aluminum hydroxide can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, or 8%.

[0064] In one embodiment, the average particle size of aluminum hydroxide is 5 μm to 15 μm. Optionally, the average particle size of aluminum hydroxide can be 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, or 15 μm.

[0065] In one embodiment, the flame retardant filler includes magnesium hydroxide, and in the coating, the mass proportion of magnesium hydroxide is 1% to 8%. Optionally, the mass proportion of magnesium hydroxide can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, or 8%.

[0066] In one embodiment, the average particle size of the magnesium hydroxide is 5 μm to 15 μm. Optionally, the average particle size of the magnesium hydroxide may be 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, or 15 μm.

[0067] In one embodiment, the flame retardant filler includes ceramic powder. Specifically, ceramic powder has good compatibility and ceramic properties, so adding ceramic powder to the coating can improve the fire retardancy of the prepared coating.

[0068] In one embodiment, in the coating, the mass proportion of the ceramic powder is 0% to 8%. Optionally, the mass proportion of the ceramic powder is 0%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, or 8%.

[0069] In one embodiment, the flame retardant filler includes sericite. Specifically, sericite is a silicate mineral with a layered structure. Sericite is not only high in strength, but also has the characteristics of being elastic, bendable, and having good abrasion resistance and wear resistance. Moreover, the chemical properties of sericite are stable, and it is difficult for acids and alkalis to react with it, so it is acid- and alkali-resistant and corrosion-resistant. The sericite lattice is stable, the volume resistivity and surface resistivity of the mineral are both high, it has low dielectric loss, is arc-resistant, corona-resistant, and has high insulation strength. In addition, sericite is a monoclinic crystal with a large diameter-to-thickness ratio, and has a strong shielding and scattering effect on visible light. In particular, sericite is also extremely heat-resistant, its performance does not change at a high temperature of 550°C, and its thermal expansion coefficient is small, with a melting point of more than 1260°C. Therefore, adding sericite to the coating can improve the comprehensive performance of the formed coating.

[0070] In one embodiment, in the coating, the mass proportion of sericite is 0% to 8%. Optionally, the mass proportion of sericite can be 0%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, or 8%.

[0071] In one embodiment, the average particle size of the sericite is 10 μm to 20 μm. Optionally, the average particle size of the sericite may be 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, or 20 μm.

[0072] In one embodiment, the flame retardant filler includes hollow glass microspheres, and in the coating, the mass proportion of the hollow glass microspheres is 0% to 8%. Optionally, the mass proportion of the hollow glass microspheres can be 0%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, or 8%.

[0073] In one embodiment, the average particle size of the hollow glass microspheres is 35 μm to 60 μm. The average particle size of the hollow glass microspheres may be 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, or 60 μm.

[0074] In one embodiment, the inorganic filler includes an oxide filler, and in the coating, the mass proportion of the oxide filler is 10% to 30%. Optionally, the mass proportion of the oxide filler can be 10%, 12%, 14%, 16%, 18%, 20%, 22%, 24%, 26%, 28%, 30%. Adding oxide fillers to the coating can improve the temperature resistance of the coating on the one hand, and the oxide filler can also maintain structural stability at a temperature higher than the decomposition temperature of phenolphthalein polyetherketone; on the other hand, the oxide filler can improve the wear resistance and corrosion resistance of the coating (coating).

[0075] In one embodiment, the oxide filler includes aluminum oxide, and in the coating, the weight percentage of aluminum oxide is 0% to 20%. Optionally, the weight percentage of aluminum oxide can be 0%, 2%, 4%, 6%, 8%, 10%, 12%, 14%, 16%, 18%, or 20%.

[0076] In one embodiment, the average particle size of the aluminum oxide is 5 μm to 25 μm. The average particle size of the aluminum oxide may be 5 μm, 6 μm, 8 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, 20 μm, 22 μm, 24 μm, or 25 μm.

[0077] In one embodiment, the oxide filler includes boron oxide, and in the coating, the mass proportion of boron oxide is 0% to 5%. Optionally, the mass proportion of boron oxide can be 0%, 1%, 2%, 3%, 4%, or 5%.

[0078] In one embodiment, the average particle size of the boron oxide is 10 μm to 25 μm. The average particle size of the boron oxide may be 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, 20 μm, 22 μm, 24 μm, or 25 μm.

[0079] In one embodiment, the inorganic filler includes zirconium oxide, and in the coating, the mass proportion of zirconium oxide is 0% to 5%. Optionally, the mass proportion of zirconium oxide can be 0%, 1%, 2%, 3%, 4%, or 5%.

[0080] In one embodiment, the average particle size of zirconium oxide is 10 μm to 20 μm. The average particle size of zirconium oxide may be 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, or 20 μm.

[0081] In one embodiment, the oxide filler includes zirconium oxide, and in the coating, the mass proportion of zirconium oxide is 0% to 5%. Optionally, the mass proportion of zirconium oxide can be 0%, 1%, 2%, 3%, 4%, or 5%.

[0082] In one embodiment, the average particle size of zirconium oxide is 10 μm to 20 μm. The average particle size of zirconium oxide may be 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, or 20 μm.

[0083] In one embodiment, the oxide filler includes zinc oxide, and in the coating, the mass proportion of zinc oxide is 0% to 5%. Optionally, the mass proportion of zinc oxide can be 0%, 1%, 2%, 3%, 4%, or 5%.

[0084] In one embodiment, the average particle size of zinc oxide is 10 μm to 20 μm. The average particle size of zinc oxide may be 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, or 20 μm.

[0085] In one embodiment, the inorganic filler includes silicon micropowder. Specifically, silicon micropowder is a micropowder made from natural quartz (SiO2) or fused quartz (amorphous SiO2 after natural quartz is melted at high temperature and cooled) through multiple processes such as crushing, ball milling (or vibration, air flow milling), flotation, acid washing and purification, and high-purity water treatment. Microsilica powder is added to the coating to improve the hardness, wear resistance, heat resistance, dimensional stability and other properties of the material; and microsilica powder also has the advantages of higher dielectric properties, low thermal expansion coefficient, low thermal conductivity, and corrosion resistance.

[0086] In one embodiment, in the coating, the mass proportion of silicon micropowder is 10% to 20%. Optionally, the mass proportion of silicon micropowder can be 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%.

[0087] In one embodiment, the average particle size of the silicon powder is 10 μm to 20 μm. The average particle size of the silicon powder can be 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, or 20 μm.

[0088] Meeting the above-mentioned range for the mass ratio of the inorganic filler can ensure that the mix ratio of organic materials and inorganic materials is within an appropriate range, thereby ensuring that the coating has stable temperature resistance within 600°C and avoiding the problem of poor compatibility of materials; and avoiding the problem of cracks and damage to the coating at high temperatures.

[0089] When the particle size of the inorganic filler is within the above range, it can be ensured that the inorganic filler particles are not easy to agglomerate, and the preparation process is simple and the cost is low; and it can also be ensured that the formed coating has good uniformity and high surface flatness.

[0090] In one embodiment, the coating further comprises a curing agent. Specifically, the curing agent may include one or more of diethylamine triamine, triethylenetetramine, tetraethylenepentamine, divinylpropylamine, menthane diamine, isophorone diamine, N-aminoethylpiperazine, bis(4-amino-3-methylcycloethyl)methane, and bis(4-aminocycloethyl)methane.

[0091] In one embodiment, in the coating, the mass proportion of the curing agent is 1% to 8%. Optionally, the mass proportion of the curing agent can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, or 8%.

[0092] In one embodiment, the coating further comprises a coupling agent. Specifically, the coupling agent may include γ-aminopropyltriethoxysilane (KH-550), octadecyltrimethoxysilane (KH560), γ-methacryloxypropyltrimethoxysilane (KH-570), and γ-mercaptopropyltriethoxysilane (KH580).

[0093] In one embodiment, the mass proportion of the coupling agent in the coating is 1% to 8%. Optionally, the mass proportion of the coupling agent can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, or 8%.

[0094] In one embodiment, the present application also provides a method for preparing a coating, please refer to Figure 3 , including the following steps:

[0095] Step S10, dissolving phenolphthalein type polyetherketone in a solvent to obtain a polymer solution.

[0096] Step S20, mixing the base material, the inorganic filler and the polymer solution, and obtaining the coating after mixing evenly.

[0097] Specifically, the coating preparation method requires that hydroxylated phenolphthalein polyetherketone is first dissolved in a solvent to prepare a phenolphthalein polyetherketone solution. Then, epoxy resin, silicon powder, glass powder, boron nitride, hollow glass microspheres, sericite, aluminum hydroxide, boron oxide, aluminum oxide, zirconium oxide, coupling agent, etc. are added to the hydroxylated phenolphthalein polyetherketone, and the mixture is uniformly stirred for 1 hour, and then the mixture is ground with a grinder for about 3 hours to obtain the coating.

[0098] Optionally, the solvent of the hydroxylated phenolphthalein type polyetherketone can be one or more of toluene, xylene, propylene glycol methyl ether acetate, DMAc, NMP, and DMF, and the solid content is 8% to 35%.

[0099] The technical solution of the present invention is described in detail below through specific embodiments.

[0100] Example 1

[0101] The present embodiment provides a coating, including phenolphthalein polyether ketone, epoxy resin (E-44), triethylenetetramine, KH550, glass powder, boron nitride, flame retardant filler (aluminum hydroxide), oxide filler (silicon powder, boron oxide, aluminum oxide, zirconium oxide); the weight average molecular weight of the phenolphthalein polyether ketone is 50,000.

[0102] The steps for making the coating of this embodiment are:

[0103] 1) Weigh 2.0 g of phenolphthalein type polyether ketone and dissolve it in 23 g of NMP solvent to obtain a phenolphthalein type polyether ketone solution.

[0104] 2) Add 4g epoxy resin E-44, 0.6g triethylenetetramine, 3.5g glass powder with a softening point of 400°C, 5g boron nitride, 1g aluminum hydroxide, 3g silicon powder, 0.5g boron oxide, 0.5g aluminum oxide, 0.5g zirconium oxide, and 0.8g KH550 to the phenolphthalein type polyetherketone solution and stir evenly for 1h.

[0105] 3) Grind the mixture with a grinder for 3.5 hours to obtain a high temperature resistant insulating coating.

[0106] Among them, the mass proportions of the matrix material, phenolphthalein polyether ketone and inorganic filler in the above production steps are: phenolphthalein polyether ketone (10%), epoxy resin (20%), boron nitride (25%), glass powder (17.5%), aluminum hydroxide (5%), aluminum oxide (2.5%), boron oxide (2.5%), microsilica powder (15%), and zirconium oxide (2.5%).

[0107] Example 2

[0108] This embodiment provides a coating, and the coating configuration is different from that of Embodiment 1 in that the coating adopts hydroxylated phenolphthalein type polyetherketone.

[0109] The mass proportions of the matrix material, phenolphthalein polyether ketone and inorganic filler are as follows: hydroxylated phenolphthalein polyether ketone (10%), epoxy resin (20%), boron nitride (25%), glass powder (17.5%), aluminum hydroxide (5%), aluminum oxide (2.5%), boron oxide (2.5%), microsilica powder (15%) and zirconium oxide (2.5%).

[0110] Example 3

[0111] This embodiment provides a coating, and the coating configuration is different from that of embodiment 1 in that: the phenolphthalein type polyether ketone and the hydroxylated phenolphthalein type polyether ketone in the coating each account for 50%, namely, phenolphthalein type polyether ketone (5%) and phenolphthalein type polyether ketone (5%).

[0112] The mass proportions of the matrix material, phenolphthalein polyether ketone and inorganic filler are as follows: phenolphthalein polyether ketone (5%), hydroxylated phenolphthalein polyether ketone (5%), epoxy resin (20%), boron nitride (25%), glass powder (17.5%), aluminum hydroxide (5%), aluminum oxide (2.5%), boron oxide (2.5%), microsilica powder (15%) and zirconium oxide (2.5%).

[0113] Example 4

[0114] This embodiment provides a coating, and the coating configuration is different from that of Embodiment 1 in that the mass of phenolphthalein type polyether ketone accounts for a larger proportion.

[0115] The mass proportions of the matrix material, phenolphthalein polyether ketone and inorganic filler are phenolphthalein polyether ketone (15%), epoxy resin (15%), boron nitride (25%), glass powder (17.5%), aluminum hydroxide (5%), aluminum oxide (2.5%), boron oxide (2.5%), microsilica powder (15%) and zirconium oxide (2.5%).

[0116] Example 5

[0117] This embodiment provides a coating, and the coating configuration is different from that of Embodiment 1 in that the mass proportion of phenolphthalein type polyether ketone is relatively small.

[0118] The mass proportions of the matrix material, phenolphthalein polyether ketone and inorganic filler are phenolphthalein polyether ketone (5%), epoxy resin (25%), boron nitride (25%), glass powder (17.5%), aluminum hydroxide (5%), aluminum oxide (2.5%), boron oxide (2.5%), microsilica powder (15%) and zirconium oxide (2.5%).

[0119] Example 6

[0120] This embodiment provides a coating, and the coating configuration is different from that of Embodiment 1 in that the mass proportion of the base material is relatively small.

[0121] The mass proportions of the matrix material, phenolphthalein polyether ketone and inorganic filler are phenolphthalein polyether ketone (20%), epoxy resin (10%), boron nitride (25%), glass powder (17.5%), aluminum hydroxide (5%), aluminum oxide (2.5%), boron oxide (2.5%), microsilica powder (15%) and zirconium oxide (2.5%).

[0122] Example 7

[0123] This embodiment provides a coating, and the coating configuration differs from that of Embodiment 1 in that the type of flame retardant filler is different, and the mass proportion of the oxide filler is relatively small.

[0124] The mass proportions of the matrix material, phenolphthalein polyether ketone and inorganic filler are phenolphthalein polyether ketone (10%), epoxy resin (20%), boron nitride (25%), glass powder (17.5%), aluminum hydroxide (2.5%), magnesium hydroxide (2.5%), ceramic powder (2.5%), sericite (2.5%), aluminum oxide (2.5%), boron oxide (2.5%), microsilica powder (10%) and zirconium oxide (2.5%).

[0125] Example 8

[0126] This embodiment provides a coating, and the coating configuration differs from that of Embodiment 1 in that the type of flame retardant filler is different and accounts for a larger proportion by mass, while the mass proportion of oxide filler is smaller.

[0127] The mass proportions of the matrix material, phenolphthalein polyether ketone and inorganic filler are phenolphthalein polyether ketone (10%), epoxy resin (20%), boron nitride (25%), glass powder (17.5%), aluminum hydroxide (5%), magnesium hydroxide (5%), ceramic powder (2.5%), sericite (2.5%), aluminum oxide (0.5%), boron oxide (0.5%), microsilica powder (11%) and zirconium oxide (0.5%).

[0128] Example 9

[0129] This embodiment provides a coating, and the coating configuration is different from that of Embodiment 1 in that the mass proportion of boron nitride is smaller, and the mass proportion of glass powder is larger.

[0130] The mass proportions of the matrix material, phenolphthalein polyether ketone and inorganic filler are phenolphthalein polyether ketone (10%), epoxy resin (20%), boron nitride (20%), glass powder (22.5%), aluminum hydroxide (5%), aluminum oxide (2.5%), boron oxide (2.5%), microsilica powder (15%) and zirconium oxide (2.5%).

[0131] Example 10

[0132] This embodiment provides a coating, and the coating configuration is different from that of Embodiment 1 in that the mass of boron nitride accounts for a larger proportion, and the mass of glass powder accounts for a smaller proportion.

[0133] The mass proportions of the matrix material, phenolphthalein polyether ketone and inorganic filler are phenolphthalein polyether ketone (10%), epoxy resin (20%), boron nitride (40%), glass powder (2.5%), aluminum hydroxide (5%), aluminum oxide (2.5%), boron oxide (2.5%), microsilica powder (15%) and zirconium oxide (2.5%).

[0134] Embodiment 11

[0135] This embodiment provides a coating, and the coating configuration is different from that of Embodiment 1 in that the mass proportion of glass powder is smaller, and the mass proportion of boron nitride is larger.

[0136] The mass proportions of the matrix material, phenolphthalein polyether ketone and inorganic filler are phenolphthalein polyether ketone (10%), epoxy resin (20%), boron nitride (32.5%), glass powder (10%), aluminum hydroxide (5%), aluminum oxide (2.5%), boron oxide (2.5%), microsilica powder (15%) and zirconium oxide (2.5%).

[0137] Example 12

[0138] This embodiment provides a coating, and the coating configuration is different from that of Embodiment 1 in that the mass of the glass powder accounts for a larger proportion, and the mass of the boron nitride accounts for a smaller proportion.

[0139] The mass proportions of the matrix material, phenolphthalein polyether ketone and inorganic filler are phenolphthalein polyether ketone (10%), epoxy resin (20%), boron nitride (22.5%), glass powder (20%), aluminum hydroxide (5%), aluminum oxide (2.5%), boron oxide (2.5%), microsilica powder (15%) and zirconium oxide (2.5%).

[0140] Example 13

[0141] This embodiment provides a coating, and the coating configuration is different from that of Embodiment 1 in that the weight average molecular weight of the phenolphthalein type polyether ketone is 100,000.

[0142] Embodiment 14

[0143] This embodiment provides a coating, and the coating configuration is different from that of Embodiment 1 in that the weight average molecular weight of the phenolphthalein type polyether ketone is 30,000.

[0144] Embodiment 15

[0145] This embodiment provides a coating, and the coating configuration is different from that of Embodiment 1 in that the epoxy resin is E-51 type.

[0146] Example 16

[0147] This embodiment provides a coating, and the coating configuration is different from that of Embodiment 1 in that the curing agent is tetraethylenepentamine.

[0148] Embodiment 17

[0149] This embodiment provides a coating, and the coating configuration is different from that of Embodiment 1 in that the curing agent is N-aminoethylpiperazine.

[0150] Embodiment 18

[0151] This embodiment provides a coating, and the coating configuration is different from that of Embodiment 1 in that the softening point of the glass powder is 320°C.

[0152] Embodiment 19

[0153] This embodiment provides a coating, and the coating configuration is different from that of Embodiment 1 in that the softening point of the glass powder is 430°C.

[0154] Embodiment 20

[0155] This embodiment provides a coating, and the coating configuration is different from that of Embodiment 1 in that the coupling agent is KH580.

[0156] Comparative Example 1

[0157] This comparative example provides a coating, the coating configuration is 5.7g epoxy resin E-44, 1.0g triethylenetetramine, 3.3g silica powder, 3.3g glass powder with a softening point of 400°C, 3.8g boron nitride, 1.0g sericite, 1.1g aluminum hydroxide, 0.4g boron oxide, 0.6g zirconium oxide, 0.9g KH580. No phenolphthalein type polyether ketone is added.

[0158] The mass proportions of the matrix material and inorganic filler are as follows: epoxy resin (30%), boron nitride (25%), glass powder (17.5%), aluminum hydroxide (5%), aluminum oxide (2.5%), boron oxide (2.5%), microsilica powder (15%), and zirconium oxide (2.5%).

[0159] The coatings obtained in Examples 1-20 and Comparative Example 1 were coated on a stainless steel plate substrate, and cured at 80°C for 1.5 hours and at 150°C for 1 hour to obtain a high temperature resistant insulating coating (the coating thickness was 250 μm). The stainless steel plate with the coating was subjected to coating thickness test, shear strength test, high temperature resistant insulation test, thermal conductivity test and flame retardant test.

[0160] Coating thickness test: refer to GB / T13452.2-2008 "Determination of paint and varnish film thickness" test standard.

[0161] Shear strength test: refer to GB / T7124-2008 "Determination of tensile shear strength of adhesives (rigid material to rigid material)" test standard. Choose metal plate as test material: length 100mm±0.25mm, width 25mm±0.25mm, surface treatment in the same way as coating, use high-strength adhesive to bond the sample sprayed with paint, the bonding surface is 25mm±0.25mm, the thickness of adhesive is recommended to be 0.2~0.3mm, and spacer wires or small glass balls can be used for control. If it is a wire, the wire should be parallel to the direction of force to avoid errors in the experiment.

[0162] High temperature insulation test: A 0.3mm coating is sprayed on one side of a 2mm thick metal plate (aluminum or stainless steel). The aluminum plate is quickly placed in a high temperature muffle furnace (600°C), taken out after 30 minutes, and cooled to room temperature at room temperature. The insulation test of the coating at room temperature or after heat resistance refers to the test under power frequency in Part 1 of GB / T1408.1-2016 "Electrical Strength Test Method for Insulating Materials". 3000V (normal temperature) or 1000V (after heat resistance) alternating current (AC) is applied to both ends of the electrode, and the maximum current value passing through the sample in 60s is recorded. This value is the leakage current.

[0163] Thermal conductivity test: GB / T22588-2008 "Flash method for measuring thermal diffusion coefficient or thermal conductivity" test standard is adopted.

[0164] Flame retardant performance test: Vertical flame retardant: refer to UL94-2021. Sample size: 125mm×13mm×0.18mm Sample pretreatment: The sample is placed in an environment of 23±2℃, 50±5%RH for 48h; Test steps: Flame height 20±1mm, Bunsen burner is placed at the center of the sample, the mouth of the Bunsen burner is 10±1mm away from the bottom of the sample, and the Bunsen burner is moved away at least 150mm at a speed of 300mm / sec after ignition time of 10±0.5s, and the afterflame time t1 is recorded at the same time. Ignite immediately when the afterflame stops, and move away at least 150mm at a speed of 300mm / sec after ignition time of 10±0.5s, and record the afterflame time t2 and afterburning time t3.

[0165] The test data of Examples 1-20 and Comparative Example 1 are shown in Table 1 and Table 2:

[0166] Table 1

[0167]

[0168]

[0169] Table 2

[0170]

[0171] From the test results of the embodiments and comparative examples in Tables 1 and 2, it can be found that the comparative example does not add phenolphthalein polyetherketone, and its shear strength is reduced, and the insulation after high temperature resistance is poor; on the contrary, by adding phenolphthalein polyetherketone, the coating has good high temperature resistance and insulation. Moreover, by further changing to adding hydroxylated phenolphthalein polyetherketone, the high temperature resistance and insulation of the material can be further improved.

[0172] In the description of the embodiments of the present application, it should be noted that the orientation or positional relationship of terms such as "center", "up", "down", "left", "right", "vertical", "horizontal", "inside" and "outside" are based on the orientation or positional relationship described in the accompanying drawings, and are only for the convenience of describing the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present application.

[0173] What is disclosed above is only a preferred embodiment of the present application, and it certainly cannot be used to limit the scope of rights of the present application. Ordinary technicians in this field can understand that all or part of the processes of implementing the above embodiment and equivalent changes made according to the claims of the present application are still within the scope covered by the present application.

Claims

1. A coating, characterized in that: The invention comprises a base material, a phenolphthalein type polyether ketone and an inorganic filler.

2. The coating according to claim 1, characterized in that The phenolphthalein type polyetherketone includes hydroxylated phenolphthalein type polyetherketone, and the hydroxylated phenolphthalein type polyetherketone reacts with the base material to form a cross-linked structure.

3. The coating according to claim 1, characterized in that The matrix material includes one or more of epoxy resin, polyester resin, polyurea-formaldehyde resin, polyurethane, polyimide, and phenolic resin.

4. The coating according to claim 1, characterized in that In the coating, the mass ratio of the phenolphthalein type polyether ketone, the base material and the inorganic filler is 1:(1-4):(7-20).

5. The coating according to claim 1, characterized in that The weight average molecular weight of the phenolphthalein type polyether ketone is 30,000 to 100,000.

6. The coating according to claim 1, characterized in that The inorganic filler includes glass powder. In the coating, the mass proportion of the glass powder is 10% to 20%, the softening point of the glass powder is 320° C. to 430° C., and the average particle size of the glass powder is 5 μm to 30 μm.

7. The coating according to claim 1, characterized in that The inorganic filler includes boron nitride. In the coating, the mass proportion of the boron nitride is 20% to 40%, and the average particle size of the boron nitride is 10 μm to 30 μm.

8. The coating according to claim 1, characterized in that The inorganic filler includes a flame retardant filler. In the coating, the mass proportion of the flame retardant filler is 1% to 15%.

9. The coating according to claim 8, characterized in that The flame retardant filler includes one or more of aluminum hydroxide, magnesium hydroxide, ceramic powder and sericite.

10. The coating according to claim 1, characterized in that The inorganic filler includes an oxide filler, and in the coating, the mass proportion of the oxide filler is 10% to 30%.

11. The coating according to claim 10, characterized in that The oxide filler includes one or more of aluminum oxide, boron oxide, zirconium oxide, zinc oxide, and silicon powder.

12. The coating according to claim 1, characterized in that The coating further comprises a curing agent and a coupling agent. In the coating, the mass proportion of the curing agent is 1% to 8%, and the mass proportion of the coupling agent is 1% to 8%.

13. A method for preparing a coating, characterized in that: include: dissolving phenolphthalein type polyetherketone in a solvent to obtain a polymer solution; The base material, the inorganic filler and the polymer solution are mixed to obtain the coating.

14. A sheet metal, characterized in that: include: A metal substrate and a coating applied on the metal substrate, wherein the coating is obtained by curing the coating according to any one of claims 1 to 12.

Citation Information

Patent Citations

  • Paint composition

    CN102850921A

  • Titanium-boron-containing organosilicon modified epoxy resin high-temperature-resistant insulating paint and preparation method therefor

    CN106566384A

  • Bismaleimide resin LCM (Liquid Composite Molding) composite material preform setting agent and preparation method thereof

    CN107163575A

  • Polymer insulating material for carbon brush holder and preparation method thereof

    CN113444338A

  • Phenolphthalein-based polyaryletherketone-carbon nanotube graft, preparation method thereof, polyether-ether-ketone heat-conducting composite material and preparation method of polyether-ether-ketone heat-conducting composite material

    CN114507356A